EXPERIENCES OF WOMEN EDUCATORS IN LEADERSHIP POSITIONS AT SEKWAI HIGH SCHOOL (ENHLANZENI REGION) - Shongwe, Nandi Olgah (My University, 2012)
The main focus of this report is to draw attention to the experiences of women educators in leadership positions in the high schools of Ehlanzeni Region. The aim of the study is to understand why there is less representation of women educators in the high schools of Ehlanzeni Region who are in the leadership positions. Following qualitative research three women educators who are in leadership positions were interviewed so as to get answers though getting insight into their experiences. The secondary data that was collected shows evidence of gender imbalances in leadership positions in the region, the total number of women leaders in the region, 305 women against 556 men in positions of leadership. The study shows that women in high school leadership of Ehlanzeni are still experiencing challenges of resistance mainly from men, stereotype practices and they strongly feel that they are not given a fair chance to prove themselves as leaders because most of the top structures that take decisions are still dominated by men. The study also reveals that women in leadership enjoy their roles and responsibilities because they believe they are doing a great job as leaders and as women. The study recommends that Ehlanzeni region should have gender-balanced decision making structures and establish mentorship programmes that will empower and mentor women educators. These programmes are believed to make women feel encouraged and have interest to participate in leadership positions and also to get the necessary support they might need as leaders.
MM thesis - P&DM
Keywords: Teachers and teaching; Educators; Women educators